2019
DOI: 10.1186/s43055-019-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cerebral microbleeds and other cardiovascular risk factors in elderly patients with acute ischemic stroke

Abstract: Background: Cerebral microbleeds are small, round dark-signal foci in the T2 *-weighted magnetic resonance imaging. They are encountered in cerebral amyloid angiopathy and hypertensive vasculopathy. Their prevalence is common in ischemic stroke and cerebral hemorrhage. The purpose of this study is to investigate the prevalence of CMBs and associated risk factors in the elderly patients with acute ischemic stroke. Results: Cerebral microbleeds were significantly associated with the presence of hypertension (in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…There was also no statistically significant link between age and the presence or absence of cerebral microbleeds, according to Ibrahim et al 13 . High blood cholesterol and antithrombotic medication treatment, on the other hand, were found to be the most major risk factors for CMB formation in the same study.…”
Section: Tablementioning
confidence: 85%
See 2 more Smart Citations
“…There was also no statistically significant link between age and the presence or absence of cerebral microbleeds, according to Ibrahim et al 13 . High blood cholesterol and antithrombotic medication treatment, on the other hand, were found to be the most major risk factors for CMB formation in the same study.…”
Section: Tablementioning
confidence: 85%
“…Tang et al 12 found a 24 percent prevalence of CMBs in patients with ischemic stroke, while Ibrahim et al 13 found a 29.4% prevalence of CMBs in elderly Egyptians with acute ischemic stroke. Our findings, on the other hand, surpass those of Wang et al 14 , who discovered an ischemic stroke prevalence of 5,7%.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Correlations between pulse pressure and severity of CMBs Pulse pressure (PP) was then divided into three categories; low, normal and high, while CMBs were ranked in severity according to number of micro bleeds (severity) as described by Ibrahim et al [5], and the number of micro bleeds counted in each rank and the corresponding PP quartile, Table 4. Correlation among the CMBs ranks (CMBs severity) and the PP quartiles was then determined using Spearman's rank test, to ascertain whether severity of CMBs increased with increase in PP.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…These lesions are clinically covert, yet they are radiological markers for small vessel diseases. CMBs occur in approximately 29.4% of the elderly patients [5], and are of increasing public health concern.…”
Section: Introductionmentioning
confidence: 99%